Implementation of Physical Education Teachers Learning at Special Elementary Schools in Kediri 2022 - Galih Satriyo Indrawan; M. Yanuar Rizky; Wasis Himawanto (NUSANTARA SPORTA: Jurnal Pendidikan dan Ilmu Keolahragaan, 2023)
Students with special needs are children who have abnormalities in such a way, whether physical, mental, social or a combination of the three aspects, so that in order to achieve optimal potential special education is needed which is designed to meet the educational needs of children with special needs. The researcher aims to examine the learning process by physical education teachers in Kediri district. This study uses the approach used in this research is ethnography. This study uses population and samples, so the sample of this study The sample used in this study totaled 8 physical education teachers, including data on 7 male Physical Education teachers and 1 female Physical Education teacher. The conclusion is that the process of implementing physical education learning in each school has its own characteristics -respectively, the teacher's method of teaching physical education can be said that teachers when teaching mostly at the SLB level use communication methods and a game approach when involved in the learning field for students who have difficulty imitating and following movements during physical activities, namely children who have their own disabilities, which can be said to have different abilities. different